Controle de fitopatógenos por fungos endofíticos de aroeiraação de um isolado de: Diaporthe sobre Fusarium graminearum - Nava , Francine Falcão de Macedo (2020)
Control methods of plant pathogens should be reviewed and improved in view of genetic resistance and the low efficiency of pesticides. Microorganisms such as, medicinal plants endophytes with antagonistic activity are an alternative for this control. Thus, the objective of the present study was to prospect endophytic fungi obtained from Schinus terebinthifolius with the ability to reduce the growth of plant pathogens. The screening of antifungal potential of fifteen endophytic isolates against Fusarium graminearum, Pyrenophora tritici-repentis and Phomopsis sojae was assessed by dual culture method. All of them showed antifungal activity, and Diaporthe significantly reduced the growth of the three pathogens. Diaporthe LGMF694 isolate was selected as the most promising among the isolates evaluated. Hence, methanolic crude extracts were obtained and evaluated for F. graminearum development control in vitro by diffusion on agar and in vivo by tests with wheat seed. One of the extracts from Diaporthe LGMF694 inhibited pathogen growth in vitro by 54.48% after 96 hours of contact. The endophytic fungus was identified as Diaporthe infecunda. through multilocus analysis of internal transcribed spacer (ITS) region, and partial translation elongation factor 1-alpha (TEF1), beta-tubulin (TUB), histone H3 (HIS) and calmodulin (CAL) genes. This study showed the antagonistic activity of endophytic from S. terebinthifolius, mainly Diaporthe, against the phytopathogens. Diaporthe infecunda. LGMF694 crude extract has the ability to control the mycelial growth of F. graminearum in vitro. Thus, both the endophytic fungi of S. terebinthifolius and their crude extracts have biotechnological potential to be explored by biological products and synthetic fungicides industries.